2020
DOI: 10.1002/mbo3.988
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis in Mycobacterium kansasii links a small RNA gene to colony morphology and biofilm formation and identifies 9,885 intragenic insertions that do not compromise colony outgrowth

Abstract: Mycobacterium kansasii (Mk) is a resilient opportunistic human pathogen that causes tuberculosis‐like chronic pulmonary disease and mortality stemming from comorbidities and treatment failure. The standard treatment of Mk infections requires costly, long‐term, multidrug courses with adverse side effects. The emergence of drug‐resistant isolates further complicates the already challenging drug therapy regimens and threatens to compromise the future control of Mk infections. Despite the increasingly recognized g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 86 publications
(133 reference statements)
0
36
1
Order By: Relevance
“…Currently, many more regulatory sRNA have been identified in Mycobacterium using saturated transposon mutagenesis (Budell, et al 2020). More recent studies have evidenced the importance of sRNA in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many more regulatory sRNA have been identified in Mycobacterium using saturated transposon mutagenesis (Budell, et al 2020). More recent studies have evidenced the importance of sRNA in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial analysis of the M. tb transcriptome by RNA-seq reveal the presence of at least 15 sRNAs (Westermann 2018). Currently, many more regulatory sRNA have been identified in Mycobacterium using saturated transposon mutagenesis (Budell, et al 2020). More recent studies have evidenced the importance of sRNA in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is four times higher than the estimate for M. tuberculosis and such biases could result in an overestimation of the number of essential genes in forward genetic screens in this organism. Evaluation of ΦMycoMarT7 in Mycobacterium kansasii revealed that while temperature sensitivity was maintained, plaque formation in M. kansasii was 800-fold less efficient than for M. smegmatis ( Budell et al, 2020 ). Mapping of the insertion sites for the 14,700 M. kansasii mutants revealed that 82% of the insertions in the chromosome were in open reading frames (ORFs); a similar percentage (83%) was observed for the pMK12478 plasmid present in this strain.…”
Section: Random Mutagenesis Using Transposonsmentioning
confidence: 99%
“…Most studies in NTMs have used transposon mutagenesis to select for mutants with specific phenotypes. Examples include pigmentation variants in M. marinum ( Gao et al, 2003 ), M. kansasii mutants with altered colony morphology ( Budell et al, 2020 ) and M. avium mutants with altered antibiotic susceptibility ( Cangelosi et al, 2006 ) (see Table 2 for details). The Tn phoA transposon was developed to perform more targeted screens that identify mutants with insertions in membrane or secreted proteins ( Taylor et al, 1987 ).…”
Section: Random Mutagenesis Using Transposonsmentioning
confidence: 99%
“…An initial analysis of the M. tb transcriptome by RNA-seq revealed the presence of at least 15 sRNAs (Westermann, 2018). Currently, many more regulatory sRNAs have been identified in Mycobacterium using saturated transposon mutagenesis (Budell et al, 2020). More recent studies have evidenced the importance of sRNA in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%